Chemical Interactions of Cryptic Actinomycete Metabolite 5‐Alkyl‐1, 2, 3, 4‐tetrahydroquinolines through Aggregate Formation. Issue 38 (7th August 2019) - Sugiyama, Ryosuke; Nakatani, Takahiro; Nishimura, Shinichi; Takenaka, Kei; Ozaki, Taro; Asamizu, Shumpei; Onaka, Hiroyasu; Kakeya, Hideaki
Abstract: Organisms often produce secondary metabolites as a mixture of biosynthetically related congeners. However, why are metabolites with minor chemical variations produced simultaneously? 5‐Alkyl‐1, 2, 3, 4‐tetrahydroquinolines (5aTHQs) are small, lipophilic metabolites produced by Streptomyces nigrescens HEK616 when cultured with Tsukamurella pulmonis TP‐B0596. A mixture of 5aTHQs forms aggregates that show enhanced membrane affinity and biological activity. The ability to form aggregates and membrane‐binding activity is regulated by the length of the alkyl chains. Aggregates with long alkyl chains were too stable to fuse with lipid membranes. However, if inactive 5aTHQ congener was mixed with active congener, the mixture showed increased membrane affinity, enabling cellular entry and biological activity. Therefore, it is shown that sloppiness in a biosynthetic pathway, by which minor structural variations can be produced, is functionally rational, as the metabolites show synergistic action. Abstract : 5aTHQs are small, lipophilic metabolites produced by Streptomyces nigrescens HEK616 in the combined culture. They form membrane‐active aggregates by which biological activity can be regulated.